Contralateral Posterior Chamber Phakic Intraocular Lens Implantation as Rehabilitation of Refractive Lens Exchange with a Monofocal Intraocular Lens in a Young, Nonpresbyopic, Bilateral Highly-Myopic Patient - Kepa Balparda; Claudia Marcela Vanegas-Ramírez; Laura Segura-Muñoz; Manuela Gómez-Londoño (Case Reports in Ophthalmological Medicine)
Background. Refractive errors are widespread in the human population; nowadays, numerous surgical options allow for efficient and safe correction them. One of the main elements to ensure success in this kind of intervention will depend on the careful patient and surgical approach selection. Excimer laser corneal surgery is considered by most for low to moderate ametropias. Another option, which has been suggested may be safer, is to cut a small corneal lenticule with femtosecond laser, and then extracting it through a small incision. Nevertheless, in some specific cases, such as patients with high refractive error or those with some corneal abnormality, laser corneal ablations are considered unsafe from either a biomechanical or refractive standpoint. In this kind of particular cases, Phakic Intraocular Lens (P-IOL) implantation constitutes attractive, highly predictable and safe option. Objective. The authors want to show the case of a young high-myopic woman, already pseudophakic in one eye, where the P-IOL implantation in the fellow eye yielded excellent short-term visual results, and high patient’s satisfaction, is presented. Materials. The authors present the case of a 32-years-old, highly myopic female patient underwent a Refractive Lens Exchange (RLE) with a monofocal Intraocular Lens (IOL) implantation in her left eye elsewhere, and developed severe visual issues, especially regarding near-work. Symptoms resolved through the implantation of a posterior chamber P-IOL in the contralateral eye. Results. The postoperative course was unremarkable, inflammation was mild, and visual recovery was quick. There was no need to perform any procedure on her left eye or to use any reading glasses, as unilateral effective near vision through her right eye was enough for all her daily tasks. Conclusions. RLE in young pre-presbyopic highly myopic patients may not be an advisable alternative in most cases, because of the high risks of retinal complications observed. In addition, eliminating accommodation will cause significant limitations, and multifocal IOLs currently available are far from the quality of vision that a young human crystalline lens yields. On the other hand, implantation of a P-IOL is a good option if eye conditions are optimal, as it preserves natural accommodation. In this case an EyeCryl Phakic Toric® IOL showed excellent short-term refractive predictability and safety.